Drug safety in thalassemia: lessons from the present and directions for the future. Issue 8 (3rd August 2021) - Grech, Laura; Sultana, Janet; Borg, Karen; Borg, Joseph
ABSTRACT: Introduction: Beta-thalassemia is an autosomal recessive hereditary anemia characterized by reduced or absent β-globin chain synthesis, affecting about 60, 000 people peryear. Management for β-thalassemia major includes regular blood transfusions followed by iron chelating therapy and drug targeting ineffective erythropoiesis. Areas covered: The safety of licensed drugs for the management of β-thalassemia is reviewed, using evidence from clinical trials and observational research. Such drugs include the iron chelators and the erythrocyte maturation agent luspatercept. The safety of emerging treatment, such as hydroxyurea and thalidomide is also reviewed. Expert opinion : Beta-thalassemia is arare disease, and is not surprising that there are limited studies investigating the safety of drugs used in this disease. Indeed, although observational studies are the main source of drug safety information in areal-world setting, only eleven studies were identified for iron-chelators and none of these estimated the risk of agiven safety outcome. Future work should aim to better leverage existing sources of real-world datato investigate drug safety in thalassemia.